The Influence of Product Mix, Promotion Mix and Brand Image on Consumer Purchasing Decisions of Sari Roti Products in South Tangerang - Jasmani Jasmani; Denok Sunarsi (PINISI Discretion Review, 2020)
Along with the many types of bread that appear now, one of which is white bread. Companies are required to make bread products that can meet the wishes of the community. This study aims to determine the effect of product mix, promotion mix and brand image on consumer purchasing decisions of Sari Roti products in South Tangerang. The method used was explanatory research with a sample of 96 consumers. The analysis technique uses statistical analysis with regression testing, correlation, determination, and hypothesis testing. The results of this study the product mix significantly influence consumer purchasing decisions by 30.3%, the hypothesis test obtained significance 0,000 <0.05. The promotion mix has a significant effect on consumer purchasing decisions by 41.2%, the hypothesis test obtained significance 0,000 <0.05. Brand image has a significant effect on consumer purchasing decisions by 26.8%, hypothesis testing obtained significance 0,000 <0.05. Product mix, promotion mix, and brand image simultaneously have a significant effect on consumer purchasing decisions by 49.3%, hypothesis testing obtained significance of 0,000 <0.05.